(untitled) (Journal of Hama University, 2021)
This study aimed to compare the post-operative sensitivity of conventional composites (layering technique) to bulk-fill ones (bulk-fill technique) in class II restorations. 15 patients aged 20 to 40 years were selected. Each one had 4 class II caries in molars that need restoring (60 restorations). Cases that had cavities exceeded half the distance between occlusal surface and roof of the pulp chamber radiologically were excluded. 4 types of resin composites were used with each patient (two conventional and two bulk-fill): conventional (Beautifil II, Shofu and Filtek Z350XT, 3M) and bulk-fill (Beautifill Bulk Restorative, Shofu and SonicFill 2, Kerr). Post-operative sensitivity was evaluated after 3 days, 1 week, 3 weeks and 7 weeks using visual analogue scale (VAS). Results were gathered and statistical analysis were done. Analysis showed no statistically differences between SonicFill 2 and Filtek Z350XT (P < 0.05) in all controlling periods noting that the degree of sensitivity in these two groups were at almost all periods of observation “feeling of comfort”, while there were statistically differences in Beautifil II and Beautifill Bulk Restorative (P > 0.05) noting that degree of sensitivity was dropped between 1 week and 3 weeks of observation periods and then it was maintained after 7 weeks. Results of this study showed that using SonicFill 2 (bulk-fill technique) and Filtek Z350XT (layering technique) in class II restorations was advantageous with respect to post-operative sensitivity.